Performance of foamed concrete using laterite as sand replacement - Lee, Kun Guan (2010)
Recent development in the field of concrete have led to a renewed interest in engineering properties of the concrete. Various aspects need to be considered in producing a high quality concrete. Lightweight Foam Concrete (LWC) is better characteristic than ordinary concrete and gives a lot of benefit to our life in long time period. LWC is getting popular in the construction field due to its lightness, versatility and its cost reduction potentials. The unique of LWC is does not use aggregate. But, recently the demand on used of natural sand in construction industry are increase. To overcome this problem, an alternative materials namely laterite was introduced as sand replacement to produce LWC - Laterite. in this study, LWC with density of 1600 kg/rn3 composed of cement to sand to water with ratio 2:1:1 were conducted. Each series of mix design were replaced with different percentagei of laterite namely 5%, 10% and 15% by the total weight of sand respectively. The aim of this study is to verify the effect of using percentage of laterite and curing ages subjected to the compressive strength test and modulus of elasticity (MOE) test. The results revealed that the strength improved when increases of percentage of laterite. It is also indicated that the curing ages influenced the compressive strength and modulus of elasticity. The 5% of laterite was performed as optimum mix design to produced LWC with laterite.